ANALISIS LOYALITAS BERDASARKAN TINGKAT KEPUASAN PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL NON PENERIMA BANTUAN IURAN PADA PASIEN RAWAT JALAN DI PUSKESMAS NGLETIH KOTA KEDIRI - Sandu Siyoto* Mareta Dewi Ariyanti ** (Universitas Muhammadiyah Jember, 2016)
Institution Of Social Security (BPJS) is an institution of social security in the public service, there's also a lack, thereby affecting the quality of service to the community. The purpose of this study was to analyze loyalty based on satisfaction level of participants Institution OfSocial Security Non Recipients in PuclicHealth Center Ngletih Kediri.The study design used is quantitative analytical research by cross sectional. The population as many as 258 respondents. By using simple random sampling obtained a sample of 157 respondents. The independent variable is the satisfaction while the dependent variable is loyalty.The result showed 97 respondents (61.8%) patients were not satisfied and 85 respondents (54.1%) patients were not loyal to the value of p = 0.000 α = 0,05 so that H0 rejected, which means there is influence loyalty to the Agency Participant satisfaction levels Social Security Recipients Non Dues in PuclicHealth Center Ngletih Kediri. With Exp (B) of 64.834, then the patient is loyal effect 64 times greater than patients who were not satisfied.By providing services that appropriate with patient satisfaction indicators will directly be able to create a loyal patients, so they do not easily move to the other treatment.Keywords: Satisfaction, Loyalty, participants BPJS Non Recipient Fees, Outpatient